Large-scale environmental correlates of forest tree distributions in Catalonia (NE Spain) (Global Ecology and Biogeography, 2003)
Aim To explore the environmental correlates of tree species distributions in Catalonia according to the chorological status of the species. Location The study area is the region of Catalonia, in northeastern Spain. Methods We used presence-absence data for 24 species, sampled in random plots distributed throughout forests of Catalonia. A climate model for the Catalonia region provided environmental variables. We used classiﬁcation tree analysis to explore the environmental correlates of the realized niches of tree species. The predictive accuracy of the models was assessed using the ROC curve approach. Potential distribution maps of tree species were generated for the whole Catalonia region. Results Models were ranked from low to high accuracy for the 24 species. Differences in accuracy among species were related to the chorological status of species. Zonal species, or species at the core of their range (Mediterranean and SubMediterranean species), were generally well predicted, while extrazonal species, or species at the edge of their range, were predicted only moderately well. Mediterranean species distributions showed good correlations with extreme temperatures and annual precipitation. Main conclusions The above trends conﬁrmed the difﬁculty of identifying the realized niche of species at the edges of their ranges. In contrast, Mediterranean and Sub-Mediterranean species, which were at the core of their range, were well-predicted, conﬁrming the importance of extremes of temperature and annual precipitation as effective surrogates for variables having more direct physiological roles in limiting the ability of plants to survive and grow. Maps of potential tree distributions allowed us to deﬁne suitable habitats and to highlight areas where species have been planted outside their natural distribution.

Large-scale environmental correlates of forest tree distributions in Catalonia (NE Spain) - Thuiller, Wilfried; Vayreda, Jordi; Pino, Joan; Sabaté, Santi; Lavorel, Sandra; Gracia, Carles (Global Ecology and Biogeography, 2003)
Aim To explore the environmental correlates of tree species distributions in Catalonia according to the chorological status of the species. Location The study area is the region of Catalonia, in northeastern Spain. Methods We used presence-absence data for 24 species, sampled in random plots distributed throughout forests of Catalonia. A climate model for the Catalonia region provided environmental variables. We used classiﬁcation tree analysis to explore the environmental correlates of the realized niches of tree species. The predictive accuracy of the models was assessed using the ROC curve approach. Potential distribution maps of tree species were generated for the whole Catalonia region. Results Models were ranked from low to high accuracy for the 24 species. Differences in accuracy among species were related to the chorological status of species. Zonal species, or species at the core of their range (Mediterranean and SubMediterranean species), were generally well predicted, while extrazonal species, or species at the edge of their range, were predicted only moderately well. Mediterranean species distributions showed good correlations with extreme temperatures and annual precipitation. Main conclusions The above trends conﬁrmed the difﬁculty of identifying the realized niche of species at the edges of their ranges. In contrast, Mediterranean and Sub-Mediterranean species, which were at the core of their range, were well-predicted, conﬁrming the importance of extremes of temperature and annual precipitation as effective surrogates for variables having more direct physiological roles in limiting the ability of plants to survive and grow. Maps of potential tree distributions allowed us to deﬁne suitable habitats and to highlight areas where species have been planted outside their natural distribution.
Keywords: chorology; classification tree analysis; environmental gradients; forest trees; potential distribution maps; realized niche; Spain